PENGARUH PENERAPAN PERMAINAN KECIL DALAM PEMANASAN TERHADAP KESIAPAN SISWA DALAM PEMBELAJARAN PJOK di SMPN 1 TUBAN - Erwin Yusuf Tirtana; Sasminta Christina Yuli Hartati (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
In the PJOK learning process there are various aspects that need attention, especially in the introduction of learning, namely ensuring students' readiness during warm-up. PJOK learning requires students' body conditions to be in good condition and ready to be used to move actively. A good choice is to use small games because they contain various movements and can also prepare students' concentration and also have playing activities in them. The aim of the study was to determine the effect of applying mini games in warming up on students' readiness for PJOK learning at SMPN 1 Tuban. The research used a quasi-experimental approach and the approach used was quantitative and used a one-group pre-test-post-test design. The population of this study were students of class VIII SMPN 1 Tuban with a total of 6 classes and a sample of class VII B students consisting of 32 students through the selection of cluster random sampling technique. Retrieval of data by calculating the number of HR using palpation techniques or feeling parts of the body precisely at the wrist. Use a stopwatch to count the number of beats for 30 seconds and multiply the result by two to get the number of beats per minute. Looking at the analysis of the results of the data using statistics, there is an effect of small games on the readiness of students at SMPN 1 Tuban with a significant increase. The conclusion is that there is an effect of implementing small games in warming up on students' readiness in PJOK learning at SMPN 1 Tuban.